Organizational culture in logistics companies and its impact on employee satisfaction - Čuček, Mateja (Array, 2020)
The aim of this research was to analyze organizational culture and the impact of different types of organizational cultures on employee satisfaction in the Slovenian logistics sector. Logistics is a service-oriented sector and therefore the impact of employee satisfaction on the quality of logistics service is even more important than in general. For the purpose of research, we conducted a quantitative survey, which combined the OCAI survey for the determination of organizational culture and the survey of employee satisfaction. The research results showed that organizational culture in Slovenian logistics sector has an impact on employee satisfaction. We can also confirm that type of organizational culture influences the satisfaction of employees. The clan and hierarchical type of organizational culture are dominant in Slovenian logistics sector. Employees prefer the clan culture which, accordingly, also leads to more employee satisfaction. It can be argued that employees in Slovenian logistics sector are the most dissatisfied with the type of market culture.